2021
DOI: 10.1108/pm-02-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

An updated survey of factors influencing property valuation accuracy in Australia

Abstract: PurposeThis study updates and extends the current work on the issue of accuracy of property valuation. The paper investigates the factors that contribute to property valuation inaccuracy and examines different strategies to achieve greater accuracy in practice.Design/methodology/approachAn online questionnaire was designed and administered on the Australian Property Institute (API) registered valuers, attempting to examine their perceptions on the current state of valuation accuracy in Australia. The variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In the residential property market in Abuja, inappropriate valuation methodology is perceived as the leading cause of valuation inaccuracy and is ranked first as shown in Table 9. This outcome is in tandem with those of Babawale ( 2013), Oduyemi et al (2016), Aliyu et al (2018) and Abidoye et al (2021) who earlier found that use of inappropriate valuation methods is a crucial cause of error in property valuation. Babawale (2021) argued that certain valuation methods are more susceptible to errors than others with experts and professionals in the academia criticising the conventional methods of valuation for being irrational and illogical.…”
Section: Valuation Accuracy In Property Marketssupporting
confidence: 73%
See 2 more Smart Citations
“…In the residential property market in Abuja, inappropriate valuation methodology is perceived as the leading cause of valuation inaccuracy and is ranked first as shown in Table 9. This outcome is in tandem with those of Babawale ( 2013), Oduyemi et al (2016), Aliyu et al (2018) and Abidoye et al (2021) who earlier found that use of inappropriate valuation methods is a crucial cause of error in property valuation. Babawale (2021) argued that certain valuation methods are more susceptible to errors than others with experts and professionals in the academia criticising the conventional methods of valuation for being irrational and illogical.…”
Section: Valuation Accuracy In Property Marketssupporting
confidence: 73%
“…(2016), Aliyu et al. (2018) and Abidoye et al . (2021) who earlier found that use of inappropriate valuation methods is a crucial cause of error in property valuation.…”
Section: Empirical Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They characterise, among others, gender, education, professional experience, the level of pressure felt by the respondent, as well as the specificity of property valuations performed by the valuer. This set of control variables was derived from previous studies that analysed the professional activity of real estate valuers (see for example, Małkowska et al, 2019;Abidoye et al, 2021). Due to this research's international character, we added a dummy variable characterising the respondent's country.…”
Section: Econometric Model Of the Impact Of Job Satisfaction On The Level Of Ethicsmentioning
confidence: 99%
“…Mention can be made of how the world financial system relies heavily on property values produced by valuers to the extent that the domino effect of poor valuations easily triggers global financial crises (Alexandridis et al, 2019). Nonetheless, there are many questionable issues of valuation quality (Amidu et al, 2021;Newell, 2004;Titman & Trueman, 1986) arising from a litany of causes such as valuation variance, valuation errors (Abidoye et al, 2021;Adegoke, 2016;Babawale, 2013;Boyd & Irons, 2002;Bretten et al, 2001;Crosby, 2000;Dou et al, 2020;Effiong, 2015;Otegbulu & Babawale, 2011;Su, 2022), client influence (Amidu & Aluko, 2007;Cloyd & Spilker, 1999;Levy & Schuck, 2005;Newell, 2004;Nwuba et al, 2015), and the opaqueness of property transactional information upon which valuation opinions are based (Cloyd & Spilker, 1999;Levy & Schuck, 2005;Newell, 2004;Olapade & Olaleye, 2018;Su, 2022). These issues continue to stick to property valuation practice thereby derailing the progress of the valuation profession toward full operational efficiency.…”
Section: Introductionmentioning
confidence: 99%